Novel methods to address old problems :using molecular tools to advise conservation actions for two threatened and endemic freshwater turtle species of Colombia (2018)
I used molecular tools (microsatellites and restriction-site associated DNA sequencing, RAD-seq) to assess the conservation status and give management recommendations for two endemic freshwater turtle species: P. lewyana and M. dahli. In chapter 1, I provide enough evidence to show that the population of M. dahli is severely fragmented into small and isolated groups. In chapter 2, I test the prediction that population fragmentation is related to habitat fragmentation, using a landscape genomics approach. I show that the landscape matrix is restricting gene flow and that anthropogenic features, such as cities and roads, and natural features, such as rivers and wetlands, are more costly to traverse than what constitutes the majority of the matrix, open grasslands. I then test the prediction that extreme habitat loss is a driver of adaptive differentiation. I show that the populations located where open grasslands predominate are adaptively different than populations located were some forest remains. In chapter 3, I use RAD-seq to revisit previous molecular studies that assessed population structure and genetic diversity in P. lewyana. These studies seemingly indicate that P. lewyana is among the turtle species with the lowest genetic diversity and that despite being found in two geographically isolated rivers, population differentiation is subtle. With improved accuracy and precision of population genetics estimates, I show that population structure is well defined and consistent with geography, and that genetic diversity is low, but not exceptionally low. In the last chapter, I give recommendations for the management of these two endangered turtle species. For M. dahli I recommend a reassessment of its conservation status, and the implementation of a genetic rescue strategy to reduce the negative effects of population fragmentation. For P. lewyana, I argue that genetic management is not pressing yet, but that genetic monitoring should be implemented.--Tomado del Formato de Documento de Grado